Noninvasive prenatal screening (NIPS) results for participants of the eXtraordinarY babies study: Screening, counseling, diagnosis, and discordance. Issue 1 (6th October 2022) - Howell, Susan; Davis, Shanlee M.; Thompson, Talia; Brown, Mariah; Tanda, Tanea; Kowal, Karen; Alston, Amanda; Ross, Judith; Tartaglia, Nicole R.
Abstract: Sex chromosome aneuploidies (SCAs), including 47, XXY, 47, XXX, 47, XYY, and supernumerary variants, occur collectively in approximately one of 500 live births. Clinical phenotypes are highly variable resulting in previous ascertainment rates estimated to be only 10%–25% during a lifetime. Historically, prenatal SCA diagnoses were incidental findings, accounting for ≤10% of cases, with the majority of diagnoses occurring postnatally during evaluations for neurodevelopmental, medical, or infertility concerns. The initiation of noninvasive prenatal screening (NIPS) in 2012 and adoption into standardized obstetric care provides a unique opportunity to significantly increase prenatal ascertainment of SCAs. However, the impact NIPS has had on ascertainment of SCAs is understudied, particularly for those who may defer diagnostic testing until after birth. This study evaluates the timing of diagnostic testing following positive NIPS in 152 infants with SCAs and potential factors influencing this decision. Eighty‐seven (57%) elected to defer diagnostic testing after a positive NIPS until birth, and 8% (7/87) of those confirmed after birth were found to have discordant results on postnatal diagnostic testing, most of which would have influenced genetic counseling.